ADAPTASI SOSIAL EKONOMI MASYARAKAT NIAS DI RW27/RT003 KELURAHAN SAIL KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Annes Sipayung; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research purposes to investigate how Nias immigrant adapts in social and economy in Kelurahan Sail Rw27/RT003. Adaptation of social and economy of Nias community in Pekanbaru is examined through mix analysis of quantitative and qualitative. In collecting data, the researcher utilized an interview to 48 respondents. The research is proven by video record and field note.The result of the research shown that the forms of social economy adaptation are done by Nias community still closed. The adaptation being done will be opened if there is a necessity. The adaptations being done are mutual cooperation, marriage habit and religion custom. The economy adaptation can be seen through trade activity and daily work as brick maker. To maximaze the income of Nias community as the brick maker, they exploit their children and wife to increase the family income.Key Words: Adaptation, Migration, Nias